Vestibular Function After the 2016 Kumamoto Earthquakes: A Retrospective Chart Review - Miwa, Toru (Frontiers in Neurology, 2021)
This retrospective chart review aimed to examine both the vestibular function and causes of dizziness experienced by individuals following a series of major earthquakes and repetitive aftershocks. All patients with balance disorders who experienced the 2016 Kumamoto earthquakes and their aftershocks completed questionnaires relevant to balance disorders and were enrolled in this study after providing informed consent. There were 2.8 times more patients with balance disorders post the earthquake. Anxiety (P = 0.02), orthostatic dysregulation (P = 0.005), and motion sickness scores (P = 0.03) were all significantly higher after the earthquakes. A subset of participants underwent clinical equilibrium testing, showing significant deteriorations in the equilibrium test results (stabilometry: P = 0.01), cervical vestibular-evoked myogenic potentials (P = 0.04), and head-up tilt (P = 0.03) after the earthquake. The findings of this study also suggest that earthquake-induced disequilibrium may be further influenced by physical stressors, including sensory disruptions induced by earthquake vibrations, changes in the living conditions, and autonomic stress. This study increases our understanding of human equilibrium in response to natural disasters. Moreover, these findings will facilitate the management of dizziness experienced during or after such disasters. Future studies should identify strategies for mitigating autonomic dysfunction to prevent post-earthquake dizziness.